Linguistische Beitraege zur Slavistik VI. JungslavistInnen-Treffen Wien 1997 - Doleschal, Ursula; Hoffmann, Edgar (Specimina philologiae Slavicae, 1999)
The present volume is the result of the 6th Young Slavonic Meeting, which took place from 11.09. until 14.09.1997 took place for the second time in Vienna. As in the previous five volumes, this volume also documents the ongoing work and thus also the scientific progress of a group of Slavic linguists who stand between graduation and habilitation.